Keterlibatan Ayah dalam Mengasuh Anak dengan Tunagrahita - Wulandari, Sri; Anastasya, Yara Andita (Jurnal Ilmiah Psikologi (JIPSI), 2023)
Fathers have an important role in parenting but their involvement is still minimal. The study aimed to look at how fathers engage in parenting. The study uses qualitative methods with phenomenological approaches. Data collection uses observation and interview techniques. The results of this study showed that two subjects were not involved in parenting, while the other subject was involved in parenting such as taking an afternoon walk, which corresponds to the paternal dimension of engagement. Three subjects also still supervised the child even though they rarely played with children, it corresponded to the dimensions of accessibility/availability. Three subjects also tried to meet the needs of children such as daily needs and children's education, it is in accordance with the dimensions of responsibility. Based on psychological well-being factors, the whole subject also accepts the child's state despite the time and process. Based on personality factors, when the child makes a mistake, the whole subject is able to manage emotions well. Two out of three subjects said that childcare was a must-do together, while one subject handed childcare to the wife for work, which was part of the attitude factor. Three subjects learned sincerely to accept the condition of their deaf children as a trust from God, it goes into the religious factor.